Multilayer structure, roll-shaped structure and packaging material
By adopting a multi-layer structure in the packaging material and using a polymer combination of low and high glass transition temperatures, the blockage problem of pigment layer and resin layer is solved when contacting the resin layer is achieved, and good Barrier performance is achieved.
Patent Information
- Application Number
- JP2024541213
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-01
- Filing Date
- 2024-02-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-02-27
AI Technical Summary
In packaging materials, the pigment layer is prone to blockage when it comes into contact with the resin layer, resulting in surface defects and degradation of Barrier performance.
A multi-layer structure is adopted, where the paper base material has a pigment layer (layer A) on one side and a layer (layer B) consisting of a low glass transition temperature polymer (a) and a high glass transition temperature polymer (b) on the other side, where the polymer (b) content is between 1 to 50 parts mass per 100 parts mass of polymer (a).
It effectively suppresses the adhesion of the pigment layer to the resin layer, avoids blockage, and improves the Barrier performance of the packaging material.
Smart Images

Figure 0007665104000004 
Figure 0007665104000001 
Figure 0007665104000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a multilayer structure, a roll-shaped structure, and a packaging material. [Background technology]
[0002] Packaging materials in which a paper base material is provided with water vapor barrier properties, gas barrier properties, oil resistance, etc. have been conventionally used in packaging foods, etc. Patent Document 1 describes a packaging material in which a water vapor barrier layer, a gas barrier layer, and a heat seal layer are laminated in this order on at least one side of a paper base material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2021-20398 Summary of the Invention [Problem to be solved by the invention]
[0004] It is common for various printing methods to be applied to the surface of packaging materials for food, etc. For this reason, a pigment layer may be provided on at least one surface of a paper substrate for the purpose of improving printability, aesthetic appearance, smoothness, etc.
[0005] When one or more resin layers are provided on the other surface of a paper base material having a pigment layer provided on one surface thereof by coating or the like, a long multilayer structure in the middle of production may be wound up into a roll after each resin layer is provided. In addition, a completed long multilayer structure is generally stored in a rolled state. When an unfinished or completed multilayer structure is rolled up in such a manner, defects may occur on the surface of the resin layer. Defects on the surface of the resin layer may not only result in poor appearance, but also lead to a decrease in various desired barrier properties, etc. Regarding the occurrence of defects on the surface of the resin layer, the inventors have found that the main cause is blocking occurring between the pigment layer and the resin layer when the two layers come into contact with each other, causing the pigment on the surface of the pigment layer to adhere to the resin layer, and that adhesion of the pigment occurs significantly in the case of a resin layer in which a polymer with a low glass transition temperature is used, such as a heat seal layer.
[0006] An object of the present invention is to provide a multilayer structure and a roll-shaped structure in which adhesion of pigments to a resin layer is suppressed and which have good barrier properties, and to provide a packaging material using such a multilayer structure. [Means for solving the problem]
[0007] The above issues are: [1] A multilayer structure having a paper base material, a layer A laminated on one side of the paper base material, and a layer B laminated on the other side of the paper base material, wherein the layer A contains a pigment, the layer B contains a polymer (a) having a glass transition temperature of 25° C. or lower and a polymer (b) having a glass transition temperature of 30° C. or higher, and the content of the polymer (b) is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polymer (a); [2] The multilayer structure of [1], wherein both the polymer (a) and the polymer (b) are water-soluble or water-dispersible; [3] The multilayer structure according to [1] or [2], wherein the total content of the polymer (a) and the polymer (b) in the layer B is 20% by mass or more and 100% by mass or less; [4] The multilayer structure of any one of [1] to [3], wherein the polymer (b) is a vinyl alcohol-based polymer; [5] The multilayer structure according to [4], wherein the degree of saponification of the vinyl alcohol polymer is 80 mol % or more and 100 mol % or less; [6] The multilayer structure according to [4], wherein the degree of saponification of the vinyl alcohol polymer is more than 96 mol % and not more than 100 mol %; [7] The multilayer structure of any one of [4] to [6], wherein the vinyl alcohol polymer has a viscosity average degree of polymerization of 200 or more and 3,000 or less; [8] The multilayer structure according to any one of [1] to [7], wherein the polymer (a) contains at least one selected from the group consisting of a styrene-based polymer, a modified olefin-based polymer, and an ester-based polymer; [9] The multilayer structure of any one of [1] to [8], which has the layer A, the paper base material, a precoat layer, a barrier layer and a heat seal layer in this order, and the precoat layer is the layer B;
[10] The multilayer structure of any one of [1] to [8], which has the layer A, the paper base material, a precoat layer, a barrier layer and a heat seal layer in this order, and the heat seal layer is the layer B;
[11] The multilayer structure of any one of [1] to [8], which has the layer A, the paper base material, a precoat layer, a barrier layer and a heat seal layer in this order, and the precoat layer and the heat seal layer are the layer B;
[12] The multilayer structure according to any one of [9] to
[11] , wherein the barrier layer contains a vinyl alcohol-based polymer;
[13] A roll-shaped structure obtained by winding any one of the multilayer structures according to [1] to [8] and
[10] to
[12] , wherein the A layer and the B layer are in direct contact with each other;
[14] A packaging material comprising any one of the multilayer structures of [1] to
[12] ; The problem is solved by providing either Effect of the Invention
[0008] According to the present invention, it is possible to provide a multilayer structure and a roll-shaped structure in which adhesion of a pigment to a resin layer is suppressed and which have good barrier properties, as well as a packaging material using such a multilayer structure. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a multilayer structure according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Multilayer structure> A multilayer structure according to one embodiment of the present invention is a multilayer structure having a paper base material, a layer A laminated on one side of the paper base material, and a layer B laminated on the other side of the paper base material, wherein the layer A contains a pigment, the layer B contains a polymer (a) having a glass transition temperature of 25° C. or lower and a polymer (b) having a glass transition temperature of 30° C. or higher, and the content of the polymer (b) is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polymer (a).
[0011] The multilayer structure has good barrier properties because adhesion of the pigment to the resin layer (i.e., layer B) is suppressed. The reason why the multilayer structure has such an effect is unclear, but the following reasons are presumed. In layer B, which is a resin layer, a polymer (a) having a glass transition temperature of 25° C. or less and a polymer (b) having a glass transition temperature of 30° C. or more are contained in a predetermined amount, and thus the adhesion of the surface of layer B to the pigment at a temperature near room temperature is reduced. As a result, even when an unfinished or completed multilayer structure is rolled so that layer A and layer B are in direct contact with each other, blocking between layer A and layer B is suppressed, and adhesion of the pigment to layer B is suppressed. When adhesion of the pigment to layer B is suppressed, roughening of the surface of layer B due to the pigment is also suppressed, and good barrier properties are exhibited by layer B, etc. On the other hand, when the content of polymer (b) relative to polymer (a) in layer B is too high, the barrier properties of polymer (a) that should be exhibited may be inhibited by polymer (b). According to a multilayer structure in which the content of polymer (b) in layer B is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of polymer (a), roughness of the surface of layer B is suppressed and the effect of polymer (a) is fully exhibited, thereby enabling layer B etc. to exhibit sufficient barrier properties.
[0012] A multilayer structure 10 according to one embodiment of the present invention shown in Fig. 1 has an A layer 11, a paper substrate 12, a precoat layer 13, a barrier layer 14, and a heat seal layer 15 in this order. In the multilayer structure 10 of this embodiment, at least one of the precoat layer 13 and the heat seal layer 15 is the above-mentioned B layer. Both the precoat layer 13 and the heat seal layer 15 may be the above-mentioned B layer. The precoat layer 13 and the heat seal layer 15 may be layers having the same composition or layers having different compositions.
[0013] The multilayer structure 10 of the embodiment of FIG. 1 is a five-layer structure consisting of only the A layer 11, the paper substrate 12, the precoat layer 13, the barrier layer 14, and the heat seal layer 15. In other embodiments, the multilayer structure may further have other layers. For example, a resin layer called an overcoat layer or the like may be provided between the barrier layer 14 and the heat seal layer 15. A pigment layer or the like may be provided between the paper substrate 12 and the precoat layer 13. The multilayer structure according to one embodiment may have a three-layer structure consisting of the A layer, the paper substrate, and the B layer. For example, when the precoat layer 13 in the multilayer structure 10 of FIG. 1 is the B layer, the multilayer structure consisting of the A layer 11, the paper substrate 12, and the precoat layer 13 during the production of the multilayer structure 10 is also one embodiment of the present invention. In addition, the multilayer structure of the present invention may have three or more B layers, for example, a metal layer or the like.
[0014] In the multilayer structure according to one embodiment of the present invention, both the A layer and the B layer may be outermost layers with one surface exposed. However, for example, other layers may be laminated or printed on a part of the surface (exposed surface) of the A layer as the outermost layer. Similarly, other layers may be laminated or printed on a part of the surface (exposed surface) of the B layer as the outermost layer. Each layer of the multilayer structure will be described in detail below.
[0015] (Paper base material) The paper base material can be a general paper mainly composed of plant-derived pulp. In this specification, the term "main component" refers to the component with the highest content by mass. In addition to pulp, the paper base material may contain sizing agents, fillers, paper strength agents, retention agents, pH adjusters, drainage improvers, water-resistant agents, softeners, antistatic agents, defoamers, slime control agents, dyes, pigments, etc.
[0016] Examples of the paper substrate include kraft paper, fine paper, medium quality paper, alkaline paper, paperboard, glassine paper, semi-glassine paper, and parchment paper.
[0017] The basis weight (mass per unit area) of the paper base material is not particularly limited, but is preferably 20 g / m 2 More than 500g / m 2 Less than 30 g / m is preferable. 2 More than 300g / m 2 Less than 40 g / m is more preferable. 2 More than 200g / m 2 The following is even more preferred:
[0018] The density of the paper base material is 0.5 g / cm 3 More than 1.2g / cm 3 Less than 0.6 g / cm is preferred. 3 More than 1.0g / cm 3 The following is more preferred:
[0019] The paper base material can be produced by a known method. In addition, a commercially available paper base material can be used.
[0020] (A layer) The layer A is a layer laminated on one side of the paper base material. The layer A may be laminated directly on the paper base material, or may be laminated via another layer.
[0021] The A layer contains a pigment. The pigment is not particularly limited, and for example, a known pigment used in coated paper can be used. The pigment may be an organic pigment or an inorganic pigment, and is preferably an inorganic pigment. Examples of the pigment include light calcium carbonate, heavy calcium carbonate, kaolin, calcined kaolin, engineered kaolin, clay, talc, silica, colloidal silica, calcium sulfate, barium sulfate, titanium dioxide, zinc oxide, zinc sulfide, zinc carbonate, satin white, aluminum silicate, calcium silicate, magnesium silicate, aluminum hydroxide, alumina, magnesium carbonate, magnesium hydroxide, kaolinite, antigorite, smectite, vermiculite, and mica. Among these, clay is preferred. One or more types of pigments can be used.
[0022] The pigment content in layer A is preferably from 60% by mass to 99% by mass, more preferably from 70% by mass to 95% by mass, and may be from 75% by mass to 90% by mass.
[0023] Layer A usually contains a binder together with the pigment. For example, known binders used in coated paper can be used as the binder. Examples of binders include vinyl alcohol polymers, acrylic polymers, cellulose derivatives, starches, styrene polymers, ester polymers, olefin polymers, fluororesins, silicone resins, polyvinyl chloride, polyvinyl acetate, polyacrylamide, polyacrylic acid esters, polyvinyl butyral, polystyrene, polyamides, etc. One or more binders can be used.
[0024] The content of the binder in the layer A is preferably from 1% by mass to 40% by mass, more preferably from 5% by mass to 30% by mass, and may be from 10% by mass to 25% by mass. The total content of the pigment and the binder in the layer A is preferably from 80% by mass to 100% by mass, and may be from 90% by mass to 100% by mass.
[0025] Layer A may further contain other components other than the pigment and binder, such as a dispersant, a viscosity improver, a water retention agent, an antifoaming agent, a water resistance agent, a fluorescent dye, a coloring dye, a surfactant, a pH adjuster, an ultraviolet absorbing agent, and a metal salt.
[0026] (B layer) The B layer is a layer laminated on the opposite side of the paper substrate to the side on which the A layer is laminated. The B layer may be laminated directly on the paper substrate, or may be laminated via another layer. As described above, the B layer may be, for example, a precoat layer disposed between the paper substrate and the barrier layer, or may be a heat seal layer. The B layer may be only one layer, or may be two or more layers.
[0027] Layer B includes a polymer (a) having a glass transition temperature of 25° C. or lower and a polymer (b) having a glass transition temperature of 30° C. or higher. When polymer (a) is composed of two or more kinds of polymers, each polymer has a glass transition temperature of 25° C. or lower. Similarly, when polymer (b) is composed of two or more kinds of polymers, each polymer has a glass transition temperature of 30° C. or higher. In other words, all polymers included in layer B are classified into polymer (a) having a glass transition temperature of 25° C. or lower, polymer (b) having a glass transition temperature of 30° C. or higher, and polymer having a glass transition temperature of more than 25° C. and less than 30° C. The polymer having a glass transition temperature of more than 25° C. and less than 30° C. is an optional component.
[0028] The glass transition temperature of the polymer is measured by differential scanning calorimetry (DSC). Specifically, it can be measured by the method described in the Examples.
[0029] (Polymer (a)) The upper limit of the glass transition temperature of the polymer (a) is 25°C, preferably 20°C, more preferably 15°C, even more preferably 10°C, and even more preferably 5°C. When the glass transition temperature of the polymer (a) is equal to or lower than the above upper limit, the layer B can exhibit good bending resistance, interlayer adhesion, and the like. In addition, when the layer B is a heat seal layer, it can also exhibit good heat sealability. The lower limit of the glass transition temperature of the polymer (a) is not particularly limited, and may be, for example, -150°C, -100°C, -50°C, or -15°C.
[0030] The polymer (a) is not particularly limited as long as it is a polymer having a glass transition temperature of 25° C. or less, but it is preferable that it contains at least one selected from the group consisting of styrene-based polymers, modified olefin-based polymers, and ester-based polymers, and it is more preferable that it is at least one selected from the group consisting of styrene-based polymers, modified olefin-based polymers, and ester-based polymers. By using such a polymer as the polymer (a), the B layer can exhibit good water vapor barrier properties, etc. The polymer (a) can be used alone or in combination with two or more kinds.
[0031] (styrene polymer) The styrene polymer is a polymer containing a styrene compound as a monomer. The styrene compound refers to styrene and a compound in which the hydrogen atom of styrene is replaced with another atom or another group. Examples of the styrene compound include styrene, α-methylstyrene, vinyltoluene, and chlorostyrene, and styrene is preferred.
[0032] Examples of the styrene polymer include polystyrene, styrene-acrylic copolymers, and styrene-butadiene copolymers.
[0033] The styrene-acrylic copolymer is a copolymer of the above-mentioned styrene compound and an acrylic compound. The acrylic compound refers to (meth)acrylic acid and a compound in which the hydrogen atom of the carboxyl group constituting (meth)acrylic acid is replaced with another atom or another group. Examples of the acrylic compound include (meth)acrylic acid, (meth)acrylic acid esters, and (meth)acrylic acid salts. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate and ethyl (meth)acrylate. Examples of the (meth)acrylic acid salts include sodium (meth)acrylate. Note that "(meth)acrylic acid" means acrylic acid and methacrylic acid.
[0034] Examples of the styrene-acrylic copolymer include a styrene-(meth)acrylic acid copolymer, a styrene-(meth)acrylic acid ester copolymer, a styrene-(meth)acrylate copolymer, etc. The styrene-acrylic copolymer may further be copolymerized with other monomers.
[0035] The styrene-butadiene copolymer is a copolymer of the above-mentioned styrene compound and a butadiene compound. The butadiene compound refers to butadiene and a compound in which the hydrogen atoms of butadiene are replaced with other atoms or other groups. Examples of the butadiene compound include 1,3-butadiene, 2-methyl-1,3-butadiene (i.e., isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, etc., and 1,3-butadiene is preferred.
[0036] The styrene-butadiene copolymer is preferably a styrene-butadiene copolymer, which may further contain other monomers copolymerized therein.
[0037] As the styrene-based polymer, a styrene-butadiene-based copolymer is preferable.
[0038] (Modified olefin polymer) The modified olefin-based polymer is a polymer containing an olefin and a monomer other than an olefin as a monomer. The modified olefin-based polymer may be a copolymer of an olefin and another monomer, or may be a polyolefin post-modified with another monomer. The modified olefin-based polymer is preferably a copolymer of an olefin and another monomer.
[0039] Examples of the olefin include α-olefins such as ethylene, propylene, n-butene, and isobutylene, with ethylene being preferred.
[0040] Examples of monomers other than the olefin that constitute the modified olefin polymer include unsaturated carboxylic acid compounds, diene compounds, vinyl esters, vinyl ethers, vinyl halides, vinylidene halides, allyl compounds, etc., and preferably, unsaturated carboxylic acid compounds or vinyl esters, and more preferably, unsaturated carboxylic acid compounds.
[0041] The unsaturated carboxylic acid compound refers to an unsaturated carboxylic acid or a compound in which the hydrogen atom of the carboxyl group constituting the unsaturated carboxylic acid is replaced with another atom or another group. That is, the unsaturated carboxylic acid compound includes unsaturated carboxylic acid, unsaturated carboxylic acid ester, unsaturated carboxyl salt, unsaturated carboxylic acid anhydride, etc. in addition to unsaturated carboxylic acid. The unsaturated carboxylic acid compound is preferably a monomer having a carboxyl group or a salt thereof.
[0042] Examples of the unsaturated carboxylic acid compound include unsaturated carboxylic acids such as (meth)acrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, and butene tricarboxylic acid; unsaturated carboxylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, monoethyl itaconic acid ester, and monobutyl fumaric acid ester; unsaturated carboxylates such as sodium (meth)acrylate; and unsaturated carboxylic acid anhydrides such as maleic anhydride.
[0043] Examples of vinyl esters include vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate, with vinyl acetate being preferred.
[0044] The modified olefin polymer is preferably an olefin-unsaturated carboxylic acid copolymer or an olefin-vinyl ester copolymer, and more preferably an olefin-unsaturated carboxylic acid copolymer. The olefin-unsaturated carboxylic acid copolymer refers to a copolymer of one or more olefins and one or more unsaturated carboxylic acid compounds. The olefin-vinyl ester copolymer refers to a copolymer of one or more olefins and one or more vinyl esters. The olefin-unsaturated carboxylic acid copolymer may be called a carboxylic acid modified polyolefin. The carboxylic acid modified polyolefin may be a polyolefin having a carboxy group introduced therein. The modified olefin polymer may also be a saponified product of an olefin-vinyl ester copolymer.
[0045] The olefin-unsaturated carboxylic acid copolymer is preferably a copolymer of ethylene and an unsaturated carboxylic acid compound, more preferably a copolymer of ethylene and an unsaturated carboxylic acid or an unsaturated carboxylic anhydride. The copolymer of ethylene and an unsaturated carboxylic acid or an unsaturated carboxylic anhydride may be called a carboxylic acid-modified polyethylene. The carboxylic acid-modified polyethylene may be a polyethylene into which a carboxy group has been introduced.
[0046] As the olefin-vinyl ester copolymer, an ethylene-vinyl acetate copolymer is preferred.
[0047] The content of the olefin units in the total monomer units in the modified olefin polymer may be from 10 mol % to 99 mol %, or from 30 mol % to 95 mol %.
[0048] (Ester polymer) The ester polymer is a polymer in which one or more types of monomers are polymerized by ester bonds. Examples of the ester polymer include polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, polyglycolic acid, and aromatic liquid crystal polyester. The ester polymer may be a biodegradable ester polymer. Examples of the biodegradable ester polymer include polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, polybutylene succinate lactate, polybutylene adipate terephthalate, poly 3-hydroxybutanoic acid, and poly 3-hydroxybutanoic acid-3-hydroxyhexanoic acid.
[0049] Among the polymers (a), from the viewpoints of water vapor barrier properties, blocking resistance, and the like, styrene-based polymers or modified olefin-based polymers are preferred, styrene-based polymers are more preferred, styrene-butadiene-based copolymers are even more preferred, and styrene-butadiene copolymers are particularly preferred.
[0050] The polymer (a) is preferably a water-soluble or water-dispersible polymer. In such a case, the B layer can be efficiently formed by a coating liquid containing water as a solvent or dispersion medium. Examples of the water-soluble or water-dispersible polymer include styrene-acrylic copolymers, styrene-butadiene copolymers, olefin-unsaturated carboxylic acid copolymers, and olefin-vinyl ester copolymers. In addition, known water-soluble or water-dispersible polymers available on the market can be used.
[0051] The lower limit of the content of the polymer (a) in the B layer is preferably 20% by mass, more preferably 40% by mass, even more preferably 60% by mass, even more preferably 65% by mass, and may be 70% by mass, 75% by mass, or 80% by mass. By making the content of the polymer (a) equal to or higher than the above lower limit, the barrier property (e.g., water vapor barrier property), bending resistance, etc. can be improved. In addition, when the B layer is a heat seal layer, the heat seal property can also be improved. On the other hand, the upper limit of this content is preferably 99% by mass, more preferably 95% by mass, even more preferably 92% by mass, and even more preferably 85% by mass.
[0052] (Polymer (b)) The lower limit of the glass transition temperature of the polymer (b) is 30° C., preferably 40° C., more preferably 50° C., and even more preferably 60° C. When the glass transition temperature of the polymer (b) is equal to or higher than the above lower limit, the adhesion of the layer B to the layer A in a general temperature environment is reduced, and blocking between the layer A and the layer B is suppressed, so that adhesion of the pigment to the layer B is suppressed. The upper limit of the glass transition temperature of the polymer (b) is not particularly limited, and may be, for example, 200° C., 150° C., or 100° C.
[0053] The polymer (b) is preferably a water-soluble or water-dispersible polymer, and more preferably a water-soluble polymer. In particular, it is preferable that both the polymer (a) and the polymer (b) are water-soluble or water-dispersible polymers. In such a case, the B layer can be efficiently formed by a coating liquid containing water as a solvent or dispersion medium. Examples of the water-soluble polymer (b) include vinyl alcohol polymers and starches.
[0054] The polymer (b) is not particularly limited as long as it is a polymer having a glass transition temperature of 30° C. or more, but as described above, it is preferably a polymer having water solubility or water dispersibility, and more preferably a vinyl alcohol-based polymer. By using a vinyl alcohol-based polymer as the polymer (b), it has advantages such as improving film-forming properties and imparting toughness. The polymer (b) can be used alone or in combination of two or more kinds.
[0055] (Vinyl alcohol polymer) A vinyl alcohol polymer is a polymer having a vinyl alcohol unit (-CH2-CHOH-). A vinyl alcohol polymer is usually obtained by saponification of a vinyl ester polymer. Examples of the vinyl ester constituting the vinyl ester polymer include the various vinyl esters mentioned above as examples of monomers other than the olefin constituting the modified olefin polymer, and vinyl acetate is preferred.
[0056] The lower limit of the saponification degree of the vinyl alcohol polymer may be, for example, 60 mol%, but is preferably 80 mol%, more preferably 90 mol%, and even more preferably 95 mol%. The saponification degree of the vinyl alcohol polymer is more preferably more than 96 mol%, more preferably more than 97.0 mol%, more preferably more than 97.5 mol%, or more than 98.0 mol%. When the saponification degree of the vinyl alcohol polymer is equal to or greater than the above lower limit, the hygroscopicity is reduced, and blocking between the A layer and the B layer under high humidity can be effectively suppressed. The upper limit of the saponification degree of the vinyl alcohol polymer may be 100 mol% or 99.9 mol%. The saponification degree of the vinyl alcohol polymer is measured in accordance with JIS K 6726:1994.
[0057] The lower limit of the viscosity average polymerization degree of the vinyl alcohol polymer is preferably 200, more preferably 300, more preferably 500, and even more preferably 800. The upper limit of the viscosity average polymerization degree is preferably 3,000, more preferably 2,500, and even more preferably 2,000. When the viscosity average polymerization degree of the vinyl alcohol polymer is equal to or higher than the lower limit, the blocking resistance in the B layer is improved, the adhesion of the pigment to the B layer is further suppressed, and the film-forming property is improved and toughness can be imparted. When the viscosity average polymerization degree of the vinyl alcohol copolymer is equal to or lower than the upper limit, molding processability can be imparted, and for example, when the copolymer is made into an aqueous solution and applied to a paper substrate or the like, the copolymer can be applied at a suitable viscosity.
[0058] The viscosity average degree of polymerization of the vinyl alcohol polymer is measured in accordance with JIS K 6726:1994. Specifically, the intrinsic viscosity [η] (liters / g) of the vinyl alcohol polymer is measured in water at 30° C., and the viscosity average degree of polymerization P is calculated by the following formula using the intrinsic viscosity [η] value. Note that, when the saponification degree of the vinyl alcohol polymer is less than 99.5 mol%, it is saponified until the saponification degree reaches 99.5 mol% or more, and then the intrinsic viscosity [η] is measured. P = ([η] × 10 4 / 8.29) (1 / 0.62)
[0059] The vinyl alcohol polymer may have a monomer unit derived from a monomer other than the vinyl alcohol unit and the vinyl ester unit. Examples of the other monomer include α-olefins such as ethylene, propylene, n-butene, and isobutylene; (meth)acrylic acid and its salts; (meth)acrylic acid esters; (meth)acrylamide; (meth)acrylamide derivatives such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, diacetone(meth)acrylamide, (meth)acrylamidopropanesulfonic acid and its salts, (meth)acrylamidopropyldimethylamine and its salts or its quaternary salts, and N-methylol(meth)acrylamide and its derivatives; methyl vinyl ether, ethyl vinyl ether, vinyl ethers such as n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether, and the like; nitriles such as acrylonitrile and methacrylonitrile, and the like; vinyl halides such as vinyl chloride and vinyl fluoride, and the like; vinylidene halides such as vinylidene chloride and vinylidene fluoride, and the like; allyl compounds such as allyl acetate and allyl chloride, and the like; unsaturated dicarboxylic acids and salts or esters thereof such as maleic acid, itaconic acid, fumaric acid, and the like; vinyl silyl compounds such as vinyltrimethoxysilane, and the like;
[0060] The other monomer that may be contained in the vinyl alcohol polymer may be α-olefin or ethylene. When the vinyl alcohol polymer has an α-olefin unit, the lower limit of the content of the α-olefin unit relative to the total monomer units in the vinyl alcohol polymer may be 0.1 mol%, 0.5 mol%, 1 mol%, 2 mol%, 3 mol%, or 4 mol%. On the other hand, the upper limit of this content may be 20 mol%, 15 mol%, 12 mol%, 10 mol%, 5 mol%, or 3 mol%. The content of the α-olefin unit relative to the total monomer units is also referred to as the α-olefin modification amount. For example, the content of the ethylene unit relative to the total monomer units is also referred to as the ethylene modification amount.
[0061] The total content of vinyl alcohol units and vinyl ester units relative to all monomer units of the vinyl alcohol polymer is preferably 80 mol% or more, more preferably 90 mol% or more, and may be 95 mol% or more, 98 mol% or more, 99 mol% or more, or 100 mol%. The total content of vinyl alcohol units, vinyl ester units, and any α-olefin units relative to all monomer units of the vinyl alcohol polymer is preferably 95 mol% or more, more preferably 99 mol% or more, and may be 100 mol%.
[0062] The lower limit of the content of the polymer (b) relative to 100 parts by mass of the polymer (a) is 1 part by mass, preferably 5 parts by mass, more preferably 10 parts by mass, further preferably 20 parts by mass, and may be 30 parts by mass. By making the content of the polymer (b) relative to the polymer (a) equal to or greater than the above lower limit, adhesion of the pigment to the B layer is suppressed, and as a result, good barrier properties are exhibited. The upper limit of the content of the polymer (b) relative to 100 parts by mass of the polymer (a) is 50 parts by mass, and may be 45 parts by mass, 40 parts by mass, 35 parts by mass, or 30 parts by mass. By making the content of the polymer (b) relative to the polymer (a) equal to or less than the above upper limit, barrier properties (for example, water vapor barrier properties) and the like can be improved.
[0063] The lower limit of the content of the polymer (b) in the B layer is preferably 1% by mass, more preferably 5% by mass, even more preferably 8% by mass, even more preferably 10% by mass, even more preferably 12% by mass, and may be 15% by mass or 20% by mass. By making the content of the polymer (b) in the B layer equal to or more than the above lower limit, adhesion of the pigment to the B layer is further suppressed, and as a result, the barrier property may be improved. On the other hand, the upper limit of this content is preferably 33% by mass, more preferably 30% by mass, and may be 25% by mass or 20% by mass. By making the content of the polymer (b) in the B layer equal to or less than the above upper limit, the barrier property (for example, water vapor barrier property) can be improved.
[0064] The lower limit of the total content of the polymer (a) and the polymer (b) in the B layer is preferably 20% by mass, more preferably 40% by mass, even more preferably 60% by mass, and even more preferably 80% by mass, 90% by mass, 95% by mass, 98% by mass or 99% by mass. When the total content of the polymer (a) and the polymer (b) in the B layer is equal to or greater than the above lower limit, the advantages of using the polymer (a) and the polymer (b) in the B layer are particularly effectively exhibited, and the bending resistance and barrier properties tend to be excellent. The upper limit of the total content of the polymer (a) and the polymer (b) in the B layer may be 100% by mass, 99.9% by mass or 99% by mass.
[0065] Layer B may further contain other components other than the polymer (a) and the polymer (b). The other components include polymers other than the polymer (a) and the polymer (b), layered inorganic compounds, surfactants, wetting agents, oil repellents, defoamers, dyes, thickeners, etc. The surfactant may be an emulsifier.
[0066] For example, when the B layer contains a layered inorganic compound, the barrier properties of the multilayer structure may be further improved. Examples of the layered inorganic compound include micas, mica, talc, montmorillonite, kaolinite, vermiculite, smectite, hectorite, taeniolite, and acid clay. When the B layer contains a layered inorganic compound, the content of the layered inorganic compound in the B layer may be, for example, 1% by mass or more and 80% by mass or less. However, when the content of the layered inorganic compound in the B layer is high, the bending resistance decreases, and cracks may occur in the B layer itself or in other layers (e.g., barrier layer) directly contacting the B layer due to bending or the like. For this reason, the upper limit of the content of the layered inorganic compound in the B layer may be 50% by mass, 30% by mass, 10% by mass, 5% by mass, or 1% by mass. In one embodiment of the present invention, the B layer may not contain a layered inorganic compound.
[0067] The lower limit of the mass per unit area of one B layer is 1g / m 2 is preferred, and 2 g / m 2 More preferably, 3 g / m 2 More preferably, 5 g / m 2 It is even more preferable that the mass per unit area of one layer of layer B is equal to or more than the above lower limit, thereby improving the barrier property and the heat sealability when it is a heat seal layer. The upper limit of the mass per unit area of one layer of layer B is 100 g / m 2 is preferred, and 50 g / m 2 More preferably, 30 g / m 2 More preferably, 20 g / m 2 When the mass per unit area of one layer of layer B is equal to or less than the above upper limit, the multilayer structure can be made thinner and lighter.
[0068] (Precoat layer) The precoat layer may be the above-mentioned B layer. In addition, when another layer such as a heat seal layer is a B layer, the precoat layer does not have to be a B layer. When the precoat layer is not a B layer, it may be, for example, a layer composed of polymer (a) and other optional components. When the precoat layer is not a B layer, polymer (a) may be the main component. The specific and preferred forms of the polymer (a) contained in the precoat layer when it is not a B layer are the same as the specific and preferred forms of the polymer (a) contained in the B layer.
[0069] The lower limit of the mass per unit area of the precoat layer is 1 g / m 2 is preferred, and 2 g / m 2 More preferably, 3 g / m 2 More preferably, 5 g / m 2 It is even more preferable that the mass per unit area of the precoat layer is equal to or more than the above lower limit, so that the barrier property and the like can be improved. The upper limit of the mass per unit area of the precoat layer is 100 g / m 2 is preferred, and 50 g / m 2 More preferably, 30 g / m 2 More preferably, 20 g / m 2 When the mass per unit area of the precoat layer is equal to or less than the above upper limit, the multilayer structure can be made thinner and lighter.
[0070] (Barrier layer) The barrier layer is usually a layer having a function of suppressing the permeation of gas or water vapor, and is preferably a layer having a function of suppressing the permeation of oxygen gas or water vapor. That is, the barrier layer is preferably an oxygen barrier layer or a water vapor barrier layer. Examples of the barrier layer include a metal film such as aluminum; an inorganic oxide film such as alumina or silicon oxide; and a polymer film. The metal film and the inorganic oxide film may be a vapor deposition film or a foil. The barrier layer may include one layer selected from these, or may include two or more layers of different types. The polymer film preferably contains a water-soluble polymer, and more preferably contains a water-soluble polymer as a main component.
[0071] Examples of the water-soluble polymer include vinyl alcohol polymers, starches, cellulose derivatives, polyvinylpyrrolidone, urethane resins, polyacrylic acid and its salts, casein, polyethyleneimine, etc. Among these, the polymer used in the barrier layer is preferably a vinyl alcohol polymer or a urethane resin, and more preferably a vinyl alcohol polymer. The specific form and preferred form of the vinyl alcohol polymer that can be used in the barrier layer are the same as the specific form and preferred form of the vinyl alcohol polymer given as an example of the polymer (b) in the B layer.
[0072] The lower limit of the content of the water-soluble polymer in the polymer membrane is preferably 70% by mass, more preferably 80% by mass, and even more preferably 90% by mass, and the upper limit of this content may be 100% by mass.
[0073] The polymer film may further contain other components in addition to the water-soluble polymer, such as polymers other than the water-soluble polymer, layered inorganic compounds, dispersants, surfactants, antifoaming agents, dyes, thickeners, etc.
[0074] The lower limit of the mass per unit area of the barrier layer is 0.3 g / m 2 is preferred, and 0.5 g / m 2 More preferably, 1 g / m 2 By setting the mass per unit area of the barrier layer to the above lower limit or more, it is possible to improve the barrier properties. The upper limit of the mass per unit area of the barrier layer is 20 g / m 2 is preferred, and 10 g / m 2 More preferably, 5 g / m 2 More preferably, 3 g / m 2 When the mass per unit area of the barrier layer is equal to or less than the above upper limit, it is possible to reduce the thickness of the multilayer structure.
[0075] (Heat seal layer) The heat seal layer may be the above-mentioned layer B. When the heat seal layer is a layer containing a vinyl alcohol-based polymer as the polymer (b), there is an additional advantage that cracking of the heat seal layer is suppressed. This is thought to be due to the fact that the affinity between the barrier layer and the heat seal layer is increased when the water-soluble polymer is contained, and repelling of the coating liquid during coating to provide the heat seal layer is less likely to occur. When cracking of the heat seal layer is suppressed, the heat sealability and barrier property are further improved. In addition, when recycling the multilayer structure, the paper base material and the resin layer may be separated. When peeling the heat seal layer from the multilayer structure, if there is little cracking in the heat seal layer, peeling of the heat seal layer becomes easier, and there is also an advantage that recyclability is improved.
[0076] When another layer such as a precoat layer is layer B, the heat seal layer does not have to be layer B. When the heat seal layer is not layer B, it can be, for example, a layer composed of polymer (a) and other optional components. When the heat seal layer is not layer B, polymer (a) may be the main component. Specific and preferred forms of polymer (a) contained in a heat seal layer when it is not layer B are the same as those of polymer (a) contained in layer B.
[0077] The lower limit of the mass per unit area of the heat seal layer is 1 g / m 2 is preferred, and 2 g / m 2 More preferably, 3 g / m 2 More preferably, 5 g / m 2 It is even more preferable that the mass per unit area of the heat seal layer is equal to or more than the above lower limit, thereby improving the heat sealability, barrier property, etc. The upper limit of the mass per unit area of the heat seal layer is 100 g / m 2 is preferred, and 50 g / m 2 More preferably, 30 g / m 2 More preferably, 20 g / m 2When the mass per unit area of the heat seal layer is equal to or less than the above upper limit, the multilayer structure can be made thinner and lighter.
[0078] (Applications, etc.) The multilayer structure according to one embodiment of the present invention can be suitably used as a packaging material or the like.
[0079] The shape, size, etc. of the multilayer structure according to one embodiment of the present invention are not particularly limited. The multilayer structure may be in the form of a sheet or may be formed into a predetermined shape. The multilayer structure may be in the form of a long sheet. For example, the lower limit of the length of the multilayer structure may be, for example, 5 m, 10 m, 50 m, or 100 m. The upper limit of this length may be, for example, 1,000,000 m, or 100,000 m. The lower limit of the width of the multilayer structure may be, for example, 30 cm or 50 cm. The upper limit of this width may be, for example, 10 m or 5 m. In general, the longer the multilayer structure is, the more likely it is that the surfaces that come into contact when wound up will adhere closely to each other, and the more likely it is that the pigment will adhere to the resin layer when wound up in a state in which the pigment layer and the resin layer are in contact with each other. Therefore, when the present invention is applied to such a long multilayer structure, the advantage that the pigment is prevented from adhering to the resin layer and that the structure has good barrier properties can be particularly effectively obtained.
[0080] When the multilayer structure has a heat seal layer, it can be used in a state where it is formed into a predetermined shape (e.g., a bag shape) by heat sealing the heat seal layers together. The heat sealing method is not particularly limited, and a known method can be used, for example, heat sealing can be performed using a hot plate heat sealer, an impulse sealer, an ultrasonic sealer, a friction heat sealer, a dielectric heating sealer, etc.
[0081] (Method of manufacturing a multilayer structure) The method for producing the multilayer structure according to one embodiment of the present invention is not particularly limited, but for example, the multilayer structure can be produced by providing each layer on a paper substrate by coating. Alternatively, a commercially available coated paper in which an A layer is provided on one side of the paper substrate may be purchased and used. A multilayer structure can also be produced by providing a B layer or the like on such a coated paper. As an example, the multilayer structure 10 in FIG. 1 can be produced by the following procedure. A precoat layer 13 is provided by applying a coating liquid for forming a precoat layer to a surface of a coated paper consisting of an A layer 11 and a paper substrate 12 on which the paper substrate 12 is exposed, and then drying the coating liquid. Next, a barrier layer 14 is provided by applying a coating liquid for forming a barrier layer to the surface of the precoat layer 13, and then drying the coating liquid. Next, a heat seal layer 15 is provided by applying a coating liquid for forming a heat seal layer to the surface of the barrier layer 14, and then drying the coating liquid. After providing each layer, a process of winding up an unfinished or completed long multilayer structure into a roll may be performed. Furthermore, drying does not have to be carried out after each coating of the coating liquid, and a simultaneous multi-layer coating method may be employed.
[0082] Each coating liquid can be applied by a conventional method, for example, by using a blade coater, a bar coater, an air knife coater, a slit die coater, a gravure coater, a microgravure coater, a gate roll coater, a curtain coater, a flexo coater, a comma coater, or the like.
[0083] The method for drying the applied coating liquid is not particularly limited, and can be performed using, for example, a hot air dryer, an infrared dryer, a gas burner, a hot plate, or the like.
[0084] The solvent or dispersion medium for the coating liquid for forming each layer is not particularly limited, and water or an organic solvent (ethanol, isopropyl alcohol, methyl ethyl ketone, toluene, etc.) can be used, with water being preferred.
[0085] The solid content (solid content concentration) of the coating liquid for forming each layer is not particularly limited, but can be, for example, 3% by mass or more and 70% by mass or less, 5% by mass or more and 60% by mass or less, or 10% by mass or more and 50% by mass or less.
[0086] <Roll-shaped structure> The roll-shaped structure according to one embodiment of the present invention is a roll-shaped structure formed by winding the multilayer structure according to one embodiment of the present invention, and the A layer and the B layer are in direct contact with each other. An unfinished or completed long multilayer structure may be stored in a rolled state. For example, when the multilayer structure 10 shown in FIG. 1 is wound to form a roll-shaped structure, the A layer 11, which is the outermost layer on one side, and the heat seal layer 15, which is the outermost layer on the other side, are in direct contact with each other. When the heat seal layer 15 is the B layer, the A layer and the B layer are in direct contact with each other. When the multilayer structure shown in FIG. 1 is wound to form a roll-shaped structure, the A layer 11, which is the outermost layer on one side, and the precoat layer 13, which is the outermost layer on the other side, are in direct contact with each other. When the precoat layer 13 is the B layer, the A layer and the B layer are in direct contact with each other.
[0087] In the roll-shaped structure according to one embodiment of the present invention, even though the pigment layer, layer A, and the resin layer, layer B, are in direct contact with each other, adhesion of the pigment to the resin layer (i.e., layer B) is suppressed, and the multilayer structure has good barrier properties. Therefore, by employing the roll-shaped structure, the multilayer structure can be efficiently manufactured, stored, etc.
[0088] <Packaging material> A packaging material according to one embodiment of the present invention may include the multilayer structure according to one embodiment of the present invention or may consist of the multilayer structure according to one embodiment of the present invention.
[0089] The packaging material has a good appearance because the adhesion of the pigment to the resin layer is suppressed, and also has good barrier properties. The packaging material is usually used so that the A layer side is on the outside based on the paper base material. The packaging material may be formed into a predetermined shape by heat sealing or the like. The packaging material is suitably used as a packaging material for, for example, food, agricultural chemicals, medicines, cosmetics, medical products, electronic parts, clothing, etc. EXAMPLES
[0090] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples in any way.
[0091] (Method of measuring glass transition temperature (Tg)) The glass transition temperature of the polymer was measured by the following method. Approximately 3 mg of the measurement sample was filled into a sample pan, and the glass transition point and melting point were measured using a DSC Q2000 (manufactured by TA Instruments, Inc.). The sample was heated from 30°C to 200°C, then cooled to -90°C, held for 5 minutes, and then heated to 200°C. Both the heating and cooling rates were 10°C / min.
[0092] [Production Example 1] Production of PVA-1 A reaction vessel equipped with a stirrer, a nitrogen inlet, and an initiator addition port was charged with 1,050 g of vinyl acetate and 1,950 g of methanol, and the temperature was raised to 60°C, after which the system was replaced with nitrogen by nitrogen bubbling for 30 minutes. After adjusting the temperature inside the reaction vessel to 60°C, 1.6 g of azobisisobutyronitrile (AIBN) was added as a polymerization initiator to start polymerization. After 3 hours, when the polymerization rate reached 50%, the polymerization was stopped by cooling. Unreacted vinyl acetate monomer was removed, and methanol was added to obtain a methanol solution of polyvinyl acetate (PVAc) (concentration 30% by mass). 55.8 g of a 10% methanol solution of NaOH (molar ratio [MR] of the amount of NaOH to the vinyl acetate unit in PVAc of 0.10) was added to 400 g of the methanol solution of PVAc (120 g of PVAc in the solution), and saponification was performed at 40°C. After the addition of the NaOH methanol solution, the gelled material was pulverized with a grinder, and the saponification reaction was performed for a total of 1 hour. Then, 1,000 g of methyl acetate was added to neutralize the remaining alkali. After confirming the completion of neutralization using a phenolphthalein indicator, 1,000 g of methanol was added to the white solid obtained by filtration and left to stand at room temperature for 3 hours for washing. After repeating the above washing operation three times, the solid obtained by centrifugal deliquor was left to stand in a dryer at 70°C for 2 days to dry, thereby obtaining a vinyl alcohol polymer (PVA-1).
[0093] [Production Example 2] Production of PVA-2 A 5 L pressurized reactor equipped with a stirrer, a nitrogen inlet, an ethylene inlet, and an initiator addition inlet was charged with 2,550 g of vinyl acetate and 450 g of methanol, and the temperature was raised to 60°C. After that, the system was purged with nitrogen by nitrogen bubbling for 30 minutes. Then, the reactor pressure was increased to 2.9 kg / cm. 2 Ethylene was introduced so that the reactor pressure was 2.9 kg / cm. After adjusting the temperature inside the reactor to 60°C, 1.0 g of AIBN was added as a polymerization initiator to start polymerization. During polymerization, ethylene was introduced to keep the reactor pressure at 2.9 kg / cm. 2The polymerization temperature was maintained at 60°C. After 3 hours, when the polymerization rate reached 20%, the polymerization was stopped by cooling. The reaction vessel was opened to remove ethylene, and nitrogen gas was bubbled in. Next, unreacted vinyl acetate monomer was removed under reduced pressure, and methanol was added to obtain a methanol solution of ethylene-vinyl acetate copolymer (concentration 20% by mass). 14.9 g of a 10% methanol solution of NaOH (molar ratio [MR] of the amount of NaOH to the vinyl acetate unit in the ethylene-vinyl acetate copolymer of 0.04) was added to 400 g of the methanol solution of the ethylene-vinyl acetate copolymer (80 g of ethylene-vinyl acetate copolymer in the solution), and saponification was performed at 40°C. After the addition of the NaOH methanol solution, the gel was crushed in a crusher, and the saponification reaction was performed for a total of 1 hour. Then, 1,000 g of methyl acetate was added to neutralize the remaining alkali. After confirming the completion of neutralization using a phenolphthalein indicator, 1,000 g of methanol was added to the white solid obtained by filtration, and the white solid was left to stand at room temperature for 3 hours for washing. The above washing procedure was repeated three times, and the solid obtained by centrifugal deliquor was then left in a dryer at 70° C. for two days to obtain an ethylene-modified vinyl alcohol polymer (PVA-2).
[0094] [Production Examples 3-4] Production of PVA-3 to PVA-4 Each of the ethylene-modified vinyl alcohol polymers (PVA-3 to PVA-4) was produced in the same manner as in Production Example 2, except that the polymerization conditions and saponification conditions shown in Table 1 were changed as shown in Table 1.
[0095] The viscosity average degree of polymerization, the degree of saponification, the amount of ethylene modification (ethylene unit content), and the glass transition temperature (Tg) of the obtained PVA-1 to PVA-4 were measured. The measurement results are shown in Table 1.
[0096] [Table 1]
[0097] (Evaluation of blocking resistance) [Example 1] A coating liquid was prepared containing, as solid contents, 90% by mass of styrene-based polymer-1 (styrene-butadiene copolymer with a Tg of 3°C) as polymer (a) and 10% by mass of PVA-1 as polymer (b). In addition, clay-coated paper ("Bladepak" manufactured by Twin Rivers Paper Company) was prepared, in which a clay-coated layer (layer A) was provided on one side of the paper substrate. The above coating liquid was applied to the surface of the clay-coated paper where the paper substrate was exposed, at a dry mass of 10 g / m. 2 The clay-coated surface (layer A) was placed on the surface of layer B and dried to obtain a multilayer structure. The surface coated with clay (layer A) was placed on the surface of layer B, and the blocking resistance after applying a pressure of 1 MPa was evaluated according to the following criteria. The results are shown in Table 2. A: The layers peeled off easily. B: There was some adhesion between the layers, but they peeled off. C: It was somewhat difficult to separate the layers. D: The layers did not peel off and the paper base was torn.
[0098] [Examples 2 to 8, Comparative Examples 1 and 2] Multilayer structures were obtained and their blocking resistance was evaluated in the same manner as in Example 1, except that the type and content of the polymer used as the solid content in the coating liquid were as shown in Table 2. The results are shown in Table 2. The polymers (a) shown in Table 2 and Table 3 described later are as follows, and all of them are commercially available products. Styrene-based polymer-1: styrene-butadiene copolymer with Tg of 3°C Modified olefin polymer-1: Carboxylic acid modified polyethylene with a Tg of -23°C Modified olefin polymer-2: Carboxylic acid modified polyethylene with a Tg of -46°C
[0099] [Table 2]
[0100] [Example 9] A clay-coated paper ("Bladepak" manufactured by Twin Rivers Paper Company) was prepared, in which a clay-coated layer (layer A) was provided on one side of a paper substrate. A coating solution for forming a precoat layer was prepared containing, as solid contents, 90% by mass of styrene-based polymer-1 (polymer (a)) and 10% by mass of PVA-1 (polymer (b)). The coating solution for forming the precoat layer was applied to the exposed surface of the clay-coated paper substrate in a dry weight ratio of 10 g / m using a gravure coater. 2 The resulting multilayer structure (A layer / paper substrate / precoat layer) was wound up into a roll-shaped structure. The multilayer structure was then pulled out from the roll-shaped structure, and the surface of the precoat layer was observed with a SEM (scanning electron microscope), revealing no adhesion of pigment. A coating solution for forming a barrier layer containing only PVA-1 as a solid content was prepared. The coating solution for forming a barrier layer was applied to the surface of the precoat layer using a gravure coater at a dry weight of 2 g / m 2 The resulting intermediate multilayer structure (layer A / paper substrate / precoat layer / barrier layer) was wound up into a roll-shaped structure, and the multilayer structure was then pulled out from the roll-shaped structure. A coating solution for forming a heat seal layer was prepared containing, as solid contents, 90% by mass of styrene-based polymer-1 (polymer (a)) and 10% by mass of PVA-1 (polymer (b)). The coating solution for forming a heat seal layer was applied to the surface of the barrier layer using a gravure coater at a dry mass of 10 g / m 2 The resulting multilayer structure (A layer / paper substrate / precoat layer / barrier layer / heat seal layer) was wound up into a roll-shaped structure. The multilayer structure was then pulled out from the roll-shaped structure, and the surface of the heat seal layer was observed with a SEM (scanning electron microscope), revealing no adhesion of pigment. The moisture permeability of the multilayer structure of Example 9 (Layer A / paper substrate / precoat layer / barrier layer / heat seal layer) obtained was measured under conditions of 23°C and 85% RH, and was found to be 58 cc / (m 2The moisture permeability was measured in accordance with the cup method described in JIS Z 2080:1976, except that the temperature and humidity conditions were as described above.
[0101] [Comparative Examples 3 and 4] The multilayer structures of Comparative Examples 3 and 4 were obtained in the same manner as in Example 9, except that the types and contents of the polymers used as solid contents in the coating liquid for forming the precoat layer and the coating liquid for forming the heat seal layer were as shown in Table 3. The surface of the precoat layer in the multilayer structure during production, the surface of the heat seal layer in the obtained multilayer structure, and the moisture permeability of the obtained multilayer structure were measured in the same manner as in Example 9. The results are shown in Table 3. The appearance of the precoat layer and the heat seal layer, including Example 9, was evaluated based on observation of their surfaces according to the following criteria. A: No pigment adhesion was observed. B: Pigment adhesion was observed and the surface was rough.
[0102] [Table 3]
[0103] As shown in Table 3, in the multilayer structure of Example 9 in which the precoat layer and the heat seal layer were formed so as to contain a polymer (a) having a glass transition temperature of 25° C. or less and a polymer (b) having a glass transition temperature of 30° C. or more, and the content of the polymer (b) was 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polymer (a), adhesion of the pigment to the precoat layer and the heat seal layer was suppressed, and good barrier properties (water vapor barrier properties) were confirmed. In the multilayer structure of Comparative Example 3 in which the precoat layer and the heat seal layer were formed without containing the polymer (b) having a glass transition temperature of 30° C. or more, adhesion of the pigment to the precoat layer and the heat seal layer occurred, and the gas barrier properties were insufficient. In addition, in the multilayer structure of Comparative Example 4 in which the precoat layer and the heat seal layer were formed containing an excessive amount of the polymer (b) having a glass transition temperature of 30° C. or more, adhesion of the pigment to the precoat layer and the heat seal layer was suppressed, but the gas barrier properties were insufficient.
[0104] The coating liquid for forming the precoat layer and the coating liquid for forming the heat seal layer used in Example 9 are the same as those used in Example 1. The coating liquid for forming the precoat layer and the coating liquid for forming the heat seal layer used in Comparative Example 3 are the same as those used in Comparative Example 2. As shown in Table 2, the B layers of Examples 1 to 8, which contain a polymer (a) having a glass transition temperature of 25° C. or less and a polymer (b) having a glass transition temperature of 30° C. or more and are formed so that the content of the polymer (b) is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the polymer (a), had good blocking resistance against the A layer (evaluation of A to C). On the other hand, the B layers of Comparative Examples 1 and 2, which do not contain a predetermined amount of the polymer (b), had poor blocking resistance against the A layer (evaluation of D). It can be assumed that there is a correlation between the good blocking resistance of the B layer against the A layer and the suppression of adhesion of the pigment to the B layer. [Industrial Applicability]
[0105] The multilayer structure of the present invention can be suitably used as a packaging material. [Explanation of symbols]
[0106] 10 Multilayer structure 11 A layer 12 Paper base material 13 Precoat layer 14 Barrier Layer 15 Heat seal layer
Claims
1. A multilayer structure having a paper base material, an A layer laminated on one side of the paper base material, and a B layer laminated on the other side of the paper base material, The layer A contains a pigment, the layer B comprises a polymer (a) having a glass transition temperature of 25° C. or lower and a polymer (b) having a glass transition temperature of 30° C. or higher, and the content of the polymer (b) is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polymer (a); A multilayer structure, wherein the total content of the polymer (a) and the polymer (b) in the layer B is 20% by mass or more and 100% by mass or less.
2. A multilayer structure having a paper base material, an A layer laminated on one side of the paper base material, and a B layer laminated on the other side of the paper base material, The layer A contains a pigment, the layer B comprises a polymer (a) having a glass transition temperature of 25° C. or lower and a polymer (b) having a glass transition temperature of 30° C. or higher, and the content of the polymer (b) is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polymer (a); The multilayer structure, wherein the polymer (b) is a vinyl alcohol-based polymer, and the degree of saponification of the vinyl alcohol-based polymer is 90 mol % or more and 100 mol % or less.
3. A multilayer structure having a paper base material, an A layer laminated on one side of the paper base material, and a B layer laminated on the other side of the paper base material, The layer A contains a pigment, the layer B comprises a polymer (a) having a glass transition temperature of 25° C. or lower and a polymer (b) having a glass transition temperature of 30° C. or higher, and the content of the polymer (b) is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the polymer (a); The layer A, the paper base material, a precoat layer, a barrier layer, and a heat seal layer are included in this order, At least one of the precoat layer and the heat seal layer is the layer B, A multilayer structure, wherein the barrier layer is a water-soluble polymer which is a vinyl alcohol polymer or a urethane resin, and the content of the water-soluble polymer in the barrier layer is 70 mass % or more.
4. The multilayer structure according to claim 1 , wherein both the polymer (a) and the polymer (b) are water-soluble or water-dispersible.
5. 2. The multilayer structure according to claim 1, wherein the polymer (b) is a vinyl alcohol polymer.
6. 6. The multilayer structure according to claim 5, wherein the degree of saponification of the vinyl alcohol polymer is from 80 mol % to 100 mol %.
7. The multilayer structure according to claim 5, wherein the degree of saponification of the vinyl alcohol polymer is more than 96 mol % and not more than 100 mol %.
8. 6. The multilayer structure according to claim 5, wherein the vinyl alcohol polymer has a viscosity average degree of polymerization of 200 or more and 3,000 or less.
9. 2. The multilayer structure according to claim 1, wherein the polymer (a) comprises at least one selected from the group consisting of a styrene-based polymer, a modified olefin-based polymer, and an ester-based polymer.
10. The layer A, the paper base material, a precoat layer, a barrier layer, and a heat seal layer are included in this order, 2. The multi-layer structure of claim 1, wherein said precoat layer is said B layer.
11. The layer A, the paper base material, a precoat layer, a barrier layer, and a heat seal layer are included in this order, 2. The multi-layer structure of claim 1, wherein said heat seal layer is said B layer.
12. The layer A, the paper base material, a precoat layer, a barrier layer, and a heat seal layer are included in this order, 2. The multi-layer structure of claim 1, wherein said precoat layer and said heat seal layer are said B layers.
13. The multilayer structure according to any one of claims 10 to 12, wherein the barrier layer comprises a vinyl alcohol-based polymer.
14. A roll-shaped structure obtained by winding the multilayer structure according to any one of claims 1 to 9, 11 and 12, A rolled structure in which the A layer and the B layer are in direct contact with each other.
15. A packaging material comprising the multilayer structure according to any one of claims 1 to 12.
Citation Information
Patent Citations
Method and device for manufacturing glossy corrugated board
JP1989120332A
Coated paper for laminating aluminum foil
JP1995173795A
Laminated film and laminating method using this laminated film
JP2002121515A
Water-resistant paper
JP2005290637A
Thermally adhesive label and method for thermally activating the same
JP2009037109A